Aplikasi Pemesanan Karantina dan Pengiriman Paket Ikan PD. Masterindo Laju Abadi di Tangerang Berbasis Android - Nunu Kustian; Dudi Parulian (Teknik Informatika Universitas Pamulang, 2020)
The more technology develops, the more it creates a consumptive society pattern. Apart from shopping, the shipping sector has also experienced many developments. PD. Masterindo Laju Abadi provides shipping and quarantine services for fish shipments, where each fish sent must have a quarantine document in order to be sent. However, the management of shipping data and tracking of receipts is still done manually, causing several errors in data retrieval or in calculating bills. If this condition is allowed to drag on, then the hope to increase the company's productivity cannot be fulfilled and it is more difficult to achieve, therefore it is better if this service sector is supported by existing technology, so that it can make it easier for fish sellers to run their business. This research takes the theme of the business that is carried out by PD. Masterindo Laju Abadi, a shipping service company that collaborates with JNE and Caratina which only provides a few employees in the office division to handle a variety of different jobs, therefore it would be better if a job done by these few people can be handled properly and efficient.